CAPABILITY DEPRIVATION MEETS THE DIGITAL DIVIDE: THE URGENCY OF ACCESSIBILITY AND CONNECTIVITY IN ALLEVIATING THE POVERTY OF TOBACCO FARMERS IN INDONESIA - Aditya Wirawan; Esmi Warassih; Benny Rikardo P. Sinaga (Scientia Integritas Utama, 2022)
Although the area and production of smallholder plantation tobacco plants cover more than 99% of the total plantation area and tobacco production in Indonesia, the allocation of Tobacco Excise Production Sharing Funds (Dana Bagi Hasil Cukai Hasil Tembakau/DBHCHT) in 2017-2021 has been approximately Rp. 2.9 trillion per year, and several DBHCHT laws and regulations are adequate, but many tobacco farmers are still in poverty. Based on the statute’s normative method, conceptual, analytical, and case techniques. As the synthesis of several poverty theories affirms that poverty is the scarcity of means of livelihood or the limited level of welfare of a person or a community due to the instability of existing resources and the deprivation of basic capabilities, which results in the inability to achieve their certain functions and goals, it is essential to solving the capability deprivation and digital divide of tobacco farmers by improving the accessibility and connectivity. The Directorate General of Fiscal Balance is necessary to build a website and monitor and evaluate transparently against any obstacles to accessibility and connectivity. Two conclusions were generated. First, the deprivation of capabilities and the digital divide are causes of poverty, so it is necessary to assess alternative policies through access and connection of adequate and sustainable information and communication technologies for tobacco farmers and communities or farmer groups. Second, the government should provide the accessibility and connectivity of tobacco farmers in Indonesia by strengthening tobacco farmer groups (such as cooperatives) and strengthening the cost-effectiveness of technology and value-added service provision.